IMPLEMENTASI PASAL 138 KUHAP BAB XV PENUNTUTAN TENTANG PEMBERKASAN PERKARA ATAS PENYIDIKAN DAN PENUNTUTAN SEBUAH PERKARA (STUDI DI KEJAKSAAN NEGERI JAKARTA TIMUR) - Rahardhan Gaza Sumantri; Novita Alfian (Verstek, 2023)
This legal research aims to find out and examine problems regarding the implementation of Article 138 of the Criminal Code CHAPTER XV prosecution regarding the filing of cases for the investigation and prosecution of a case with study at (East Jakarta District Attorney), the entire process of which is included in the pre-prosecution process. This research is an empirical legal research that is descriptive in nature. Secondary data types include primary, secondary and tertiary legal materials. Primary data is the main data of this study. While secondary data is used to support primary data. Data collection techniques used were interviews and literature studies with qualitative analysis techniques. The research instrument was in the form of the provisions of Article 110 and Article 138 of the Criminal Procedure Code and Law number 8 of 1981 concerning Criminal Procedure Code, then the analytical technique used was the deductive method. From the results of the study, a conclusion can be drawn that in the case of a narcotics crime case of the methamphetamine type with the case register number: BP/57/V/2022/Res.Narcotics at the East Jakarta District Attorney's Office, then the Public Prosecutor has applied the legal provisions of Article 138 of the Criminal Procedure Code. Where the process of transferring the file by the investigator to the Public Prosecutor has been carried out and according to the provisions of Article 110 and Article 138 paragraph (2) of the Criminal Procedure Code, the Public Prosecutor after examining the case file and stating that the file is incomplete.Keywords: Pre-prosecution, Implementation, investigating officer, East Jakarta District Attorney, Independence, Public Prosecutor, investigation, prosecution